The role of community integration and empowerment for the transformative change in community mental health - Ornelas, José (2019)
The present article first presents a critique about the current status of the community mental health (CMH) field. Second, based on theoretical and empirical literature, it presents a perspective inspired by the inception of community psychology, namely the empowerment and community integration principles to offer a challenging framework to inspire reforms in the CMH field. The article also discusses two promising CMH practices, supported employment and independent housing with support, determinant for the transformation of life conditions for people experiencing mental illness while promoting people’s empowerment and integration in the community. The authors argue that CMH programs and practices focused on integration together with self-representation movements, organisations, or networks aligned with the community psychology acting principles have the potential to inform a renovated partnership within CMH stakeholders and bring about sustainable change focused on the active citizenship for people who experience mental illness.